2021
DOI: 10.18203/2320-1770.ijrcog20211149
|View full text |Cite
|
Sign up to set email alerts
|

Meconium-stained liquor and its impact on maternal and neonatal outcome

Abstract: Background: Meconium stained amniotic fluid (MSAF) is predictor of adverse fetal outcomes. However, all fetuses with meconium passage do not have an adverse outcome and it is important to distinguish those who develop fetal distress promptly to prevent and intervene the sequalae accordingly. Hence this study was undertaken to study the grades of meconium stained liquor and its effect on intrapartum management and relation with maternal and neonatal outcome.Methods: A prospective observational study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The association of MSAF with null parity is still not clear based on the demographic characteristics of the existing studies. 13,14 Our study revealed that the mean age of the women with irregular labour pains and MSAF was 28.05 years which were compared with the study conducted by Amjad and coworkers who reported the mean age of the pregnant women was 25.77. 15 Another study conducted by Tayade confirmed that mean age of the pregnant women was 23.02 years.…”
Section: Discussionmentioning
confidence: 45%
“…The association of MSAF with null parity is still not clear based on the demographic characteristics of the existing studies. 13,14 Our study revealed that the mean age of the women with irregular labour pains and MSAF was 28.05 years which were compared with the study conducted by Amjad and coworkers who reported the mean age of the pregnant women was 25.77. 15 Another study conducted by Tayade confirmed that mean age of the pregnant women was 23.02 years.…”
Section: Discussionmentioning
confidence: 45%